2017
DOI: 10.12927/hcpol.2017.25029
|View full text |Cite
|
Sign up to set email alerts
|

Facilitative Components of Collaborative Learning: A Review of Nine Health Research Networks

Abstract: Objective: Collaborative research networks are increasingly used as an effective mechanism for accelerating knowledge transfer into policy and practice. This paper explored the characteristics and collaborative learning approaches of nine health research networks. Data sources/study setting: Semi-structured interviews with representatives from eight diverse US health services research networks conducted between November 2012 and January 2013 and program evaluation data from a ninth.[20] HEALTHCARE POLICY Vol.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Such critique is in line with other studies where despite the positive perception of Padlet, students in an English remedial class felt that since the students reflected prior to positing, there was delay in the feedback posted and so the discussion on the Padlet was neither natural nor instantaneous (Chuah, 2015). The caveats (and the pros) of online collaborations within health service research networks have also been discussed (Leroy et al, 2017). Like in a previous study where not all students found Padlet to be supportive of learning (Deni and Zainal, 2015), in this study, a small fraction of students responded either 'neutral' or 'disagree' to Padlet-mediated learning benefits and commented that the presenter was more important than the tool.…”
Section: Limitations Of the Studysupporting
confidence: 60%
“…Such critique is in line with other studies where despite the positive perception of Padlet, students in an English remedial class felt that since the students reflected prior to positing, there was delay in the feedback posted and so the discussion on the Padlet was neither natural nor instantaneous (Chuah, 2015). The caveats (and the pros) of online collaborations within health service research networks have also been discussed (Leroy et al, 2017). Like in a previous study where not all students found Padlet to be supportive of learning (Deni and Zainal, 2015), in this study, a small fraction of students responded either 'neutral' or 'disagree' to Padlet-mediated learning benefits and commented that the presenter was more important than the tool.…”
Section: Limitations Of the Studysupporting
confidence: 60%
“…Presence, development and survival of trust is so vital for group performance that its effect on group outcomes has been extensively examined in the literature (Stacey, 2002;Liu, Magjuka & Lee, 2008;Mitchell & Zigurs, 2009;Van Gennip, Segers & Tillema, 2010;Fransen, Kirschner & Erkens, 2011). Mutual trust, and sense of community (Fransen Weinberger, & Kirschner, 2013;Leroy, Rittner, Johnson, Gerteis, & Miller, 2017) are defined to be as key factors to successful collaboration. In fact, building up mutual trust improves learnerlearner interaction (De Meo, Messina, Rosaci, & Sarné, 2017) or vice-versa.…”
Section: Development Of Trust Among Collaborative Learning Group Membersmentioning
confidence: 99%
“…To recap, trust is one of the most prominent factors for successful virtual collaboration (Leroy et al, 2017), and it is suggested in the literature that the effect of socio-emotional processes such as trust should be examined in a collaborative learning environment (Isohätälä, Järvenoja, & Järvelä, 2017). It is obvious that there is a need for further studies investigating trust development in such environments.…”
Section: Virtual Groupwork and Trust Buildingmentioning
confidence: 99%
“…Research has examined how organizational learning and improvement are affected by internal organizational factors, such as individual training and learning to improve work while doing it 24 : teamwork, leadership, information technology, knowledge management, and culture. 18,[25][26][27][28][29][30][31][32][33][34] Studies also identify influences on learning within an organization's operating environment, including collaboration among care organizations 35 ; partnerships with external researchers 36 ; funding for research, innovation, and other activities supporting learning 29 ; and payment for high value care and other forms of care improvement. 25,29…”
Section: Introductionmentioning
confidence: 99%